The Development of Ijma' - Muhammad Y. Faruqi (International Institute of Islamic Thought, 1992)
In the beginning, ijma' (consensus) was more a pragmatic necessity than an explicit Shari'ah principle. It was first applied to public policy considerations and was used to settle some crucial questions that had arisen (we will discuss the issue of khilafah separately, where we can see how the Companions attempted to settle this issue). The event of the Thaqifah of Banu Sa'idah was a great test for the ummah's social order and alerted the leaders to potential future crises. The Companions therefore gave immediate attention to the succession issue, and sincere people realized that the ummah needed a sociopolitical doctrine that would support its desired sociopolitical development and keep it united. Among the khulafa 'al rashidun, particularly Abu Bakr and ' Umar, great emphasis was placed on the principle of shura, which was, in fact, a means to realize ijma '. The development of ijma ' was an opportune and proper approach to preserve the ummah's unity and integrity. As the Companions were greatly concerned about the establishment of the khilafah by means of ijma', 'Umar rejected all attempts to use other methods.' Although the fuqaha' (jurists) refer to the Qur'anic ayat and the ahadith as a normative basis for ijma', precedents are found in the practice the khulafa ' al rashidun and the Companions, who made agreed-upon decisions in many social and religious matters. The jurists are unanimous in agreeing that the Companions' ijma' is a complete and definite source of law, and some recognize it to the exclusion of all other source. The classical jurist al Khatib al Baghdadi ...